Implementasi RESTful API Pada Laravel dan Simulator IoT Wokwi Untuk Pengukuran Suhu dan Kelembaban Menggunakan Metode Waterfall - Ardhana, Valian Yoga Pudya; Hidayat, Muhammad Taufiq; Jannah, Miftahul; Sumiati, Sumiati; Rini, Puspita; Sari, Nila (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research discusses the implementation of RESTful API in the Laravel web development framework, along with the utilization of the IoT Wokwi simulator for monitoring temperature and humidity. The application of the waterfall development method is employed as an approach to organize the development process with clear steps in creating the temperature and humidity measurement program. The aim of this research is to create an efficient and well-structured application program interface using Laravel, while simultaneously leveraging the IoT Wokwi simulator as a tool for testing and validating the functionality of temperature and humidity measurement. The research methodology involves the use of the software development life cycle (SDLC) model, specifically the waterfall model, as an approach to the software development life cycle. The anticipated outcome of this research is to provide practical guidance for developers in creating an effectively integrated temperature and humidity measurement system using web technology and IoT.